2013
DOI: 10.1038/bjc.2013.173
|View full text |Cite
|
Sign up to set email alerts
|

Genistein downregulates onco-miR-1260b and inhibits Wnt-signalling in renal cancer cells

Abstract: Background:Wnt-signalling has an important role in renal cancer and it is modulated by genistein in other cancers. Recently, microRNAs (miRNAs) have emerged as new regulators of gene expression. Thus, we focused on miRNAs to examine the regulatory mechanism of genistein on the Wnt-signalling pathway in renal cell carcinoma (RCC).Methods:Initially, we investigated the effect of genistein on Wnt-signalling (TOPflash reporter assay (TCF reporter assays)) in renal cancer cells, and using microarray identified cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 26 publications
9
95
0
Order By: Relevance
“…Collectively, the antitumor effects of gemcitabine in HuCCT-1 cells might be related to the reduction of these miRNAs. miR-1260b, in particular, has been recognized as an onco-miRNA, because the antitumor effect molecule genistein downregulates onco-miR-1260b and inhibits the Wnt-β-catenin signaling pathway, which is involved in cell growth (37). The Wnt-β-catenin signaling pathway is activated during CCC tumorigenesis (45).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the antitumor effects of gemcitabine in HuCCT-1 cells might be related to the reduction of these miRNAs. miR-1260b, in particular, has been recognized as an onco-miRNA, because the antitumor effect molecule genistein downregulates onco-miR-1260b and inhibits the Wnt-β-catenin signaling pathway, which is involved in cell growth (37). The Wnt-β-catenin signaling pathway is activated during CCC tumorigenesis (45).…”
Section: Discussionmentioning
confidence: 99%
“…A study showed inhibition by the phenol of β-catenin -mediated WNT signaling through gene expression by demethylating its silenced promoter in colon cancer cell lines (Zhang & Chen, 2011). A similar study with renal cancer cells also showed inhibition of Wnt-signaling, thus effecting the proliferation and renewal of cancer stem cells (Hirata, Ueno, Nakajima et al, 2013). Data showed genistein, a natural chemo-preventive agent, inhibited cell growth, clonogenicity, cell migration and invasion, epithelial-mesemchymal transition, cancer stem cell phenotype, and formation of pancreatospheres in pancreatic cancer cells (Bao, Wang, Ali et al, 2011;Bao, Wang, Ali et al, 2011).…”
Section: Figure 2 Genisteinmentioning
confidence: 91%
“…Treatment of ovarian and pancreatic cancer cells with genistein causes inhibition of cell growth and migration through suppression of miR-27a [79,80] . Furthermore, genistein upregulates the tumor suppressor miR-574-3p in prostate cancer cells [81] , and exerts its antitumor effect in prostate cancer via downregulation of miR-1260b [82] . Genistein treatment downregulates oncogenic miR-1260b and results in inhibition of Wnt-signaling in renal cancer cells [82] .…”
Section: Genisteinmentioning
confidence: 99%
“…Furthermore, genistein upregulates the tumor suppressor miR-574-3p in prostate cancer cells [81] , and exerts its antitumor effect in prostate cancer via downregulation of miR-1260b [82] . Genistein treatment downregulates oncogenic miR-1260b and results in inhibition of Wnt-signaling in renal cancer cells [82] . Additionally, miR-223 expression is downregulated in pancreatic cancer cells after genistein treatment that correlated with cell growth inhibition and induction of apoptosis [83] .…”
Section: Genisteinmentioning
confidence: 99%